Fluorinated networks dynamics studied by means of broadband dielectric spectroscopy - Miccio, Luis Alejandro (2015)
The influence of the surface chemical modification on the bulk behavior of epoxy based networks has been studied. In particular, the bulk dynamics of epoxy-amine networks modified with fluorinated side chains has been characterized by means of broadband dielectric spectroscopy (BDS), differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR) spectroscopy. The fluorination effect on the structure and dynamics of the materials has been related with the observed changes in both segmental and secondary relaxations. An acceleration of the segmental dynamics as the fluorination degree increases has been clearly observed. As a result, a compromise between fluorine surface enrichment and bulk modification has been proposed for these materials.